Analisis Minat Belajar Mahasiswa FKIP Universitas Papua pada Pembelajaran Online - Cendy Chaterina Manopo; Sri Wahyu Widyaningsih; Sri Rosepda Br. Sebayang (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to analyze the learning interests of FKIP University Papua students in online learning. The research method used is a survey method using a questionnaire. The sampling technique used was purposive sampling, with a sample of 100 students from all study programs in the FKIP, University of Papua. The instrument used in this study was a student learning interest questionnaire consisting of 15 statements. The results of the analysis show that the level of interest in learning from Papua University FKIP students falls into three categories. On the indicator of pleasure, the results of interest in learning are very high as much as 23%, categories of high interest in learning as much as 56%, and categories of interest in learning as much as 19%, and low category as much as 2%. In the indicator of interest, it was found that the results of interest in learning were very high as much as 22%, categories of high interest in learning as much as 64%, categories of interest in learning as much as 13%, and low category as much as 1%. In the indicator of attention, the results of interest in learning were very high as much as 8%, the category of high interest in learning was 61%, the category of interest in learning was 29%, and the category for the low category was 2%. The most visible learning interest is interest in learning with an indicator of interest, namely a sense of interest in solving the questions given during online learning.